2020
DOI: 10.3390/s20226526
|View full text |Cite
|
Sign up to set email alerts
|

Deep-Asymmetry: Asymmetry Matrix Image for Deep Learning Method in Pre-Screening Depression

Abstract: To have an objective depression diagnosis, numerous studies based on machine learning and deep learning using electroencephalogram (EEG) have been conducted. Most studies depend on one-dimensional raw data and required fine feature extraction. To solve this problem, in the EEG visualization research field, short-time Fourier transform (STFT), wavelet, and coherence commonly used as method s for transferring EEG data to 2D images. However, we devised a new way from the concept that EEG’s asymmetry was considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 26 publications
(38 reference statements)
0
30
1
Order By: Relevance
“…Kang M et al [39] introduced a novel methodology of feature extraction to detect depression which was exploiting asymmetry feature of EEG signals and converting it into 2D images to feed to the convolutional neural network. In the preprocessing level, each channel of raw EEG signals normalized by the min-max normalization method, and then artifacts elimination was done by the independent component analysis (ICA).…”
Section: Deep Learning Methods For Depression Detection Using Eeg Signalsmentioning
confidence: 99%
“…Kang M et al [39] introduced a novel methodology of feature extraction to detect depression which was exploiting asymmetry feature of EEG signals and converting it into 2D images to feed to the convolutional neural network. In the preprocessing level, each channel of raw EEG signals normalized by the min-max normalization method, and then artifacts elimination was done by the independent component analysis (ICA).…”
Section: Deep Learning Methods For Depression Detection Using Eeg Signalsmentioning
confidence: 99%
“…Kang M et al [40] introduced a novel methodology of feature extraction to detect depression which was exploiting asymmetry feature of EEG signals and converting it into 2D images to feed to the convolutional neural network. In the preprocessing level, each channel of raw EEG signals normalized by the min-max normalization method, and then artifacts elimination was done by the independent component analysis (ICA).…”
Section: Deep Learning Methods For Depression Detection Using Eeg Signalsmentioning
confidence: 99%
“…This is a typical pattern seen in relaxed adults and is better visible after the age of 13 [34]. Using the alpha asymmetry image, Kang et al found the best performance for the classification model for detecting depression [36].…”
Section: Fig 2 Different Frequency Bands Of Eeg (Adopted From [31])mentioning
confidence: 96%